Innate immune response in the gut against Salmonella - review - Trebichavský, I; Splíchal, I; Splíchalová, A (Folia microbiologica, 2010)
Innate immunity is shaped by a complex of redundant and pleiotropic factors that ensure recognition, alert and suppression of pathogens. Innate immune responses in the gut are complicated by the requirement of parallel tolerance to commensal microflora predominating in cell numbers and species. In normal individuals, the intestinal mucosa together with relevant lymph nodes represents a robust barrier against systemic spread of non-typhoid Salmonella. Contemporary insights into these defense mechanisms are reviewed.
Keywords: Immunity, Mucosal; Animals; Intestinal Mucosa; přirozená imunita; lidé; zvířata; Salmonella; Gastrointestinal Tract; gastrointestinální trakt; slizniční imunita; salmonelóza; střevní sliznice; Immunity, Innate; Salmonella Infections; Humans